Early effects of a high-caloric diet and physical exercise on brain volumetry and behavior: a combined MRI and histology study in mice - Sack, Markus; Sartorius, Alexander; Gass, Peter (Brain imaging and behavior, 2017)
Excessive intake of high-caloric diets as well as subsequent development of obesity and diabetes mellitus may exert a wide range of unfavorable effects on the central nervous system (CNS) in the long-term. The potentially harmful effects of such diets were suggested to be mitigated by physical exercise. Here, we conducted a study investigating early effects of a cafeteria-diet on gray and white brain matter volume by means of voxel-based morphometry (VBM) and region-of-interest (ROI) analysis. Half of the mice performed voluntary wheel running to study if regular physical exercise prevents unfavorable effects of a cafeteria-diet. In addition, histological analyses for myelination and neurogenesis were performed. As expected, wheel running resulted in a significant increase of gray matter volume in the CA1-3 areas, the dentate gyrus and stratum granulosum of the hippocampus in the VBM analysis, while a positive effect of the cafeteria-diet was shown for the whole hippocampal CA1-3 area only in the ROI analysis, indicating a regional volume effect. It was earlier found that hippocampal neurogenesis may be related to volume increases after exercise. Interestingly, while running resulted in a significant increase in neurogenesis assessed by doublecortin (DCX)-labeling, this was not true for cafeteria diet. This indicates different underlying mechanisms for gray matter increase. Moreover, animals receiving cafeteria diet only showed mild deficits in long-term memory assessed by the puzzle-box paradigm, while executive functioning and short term memory were not affected. Our data therefore highlight that high caloric diet impacts on the brain and behavior. Physical exercise seems not to interact with these mechanisms.
Published online: 12 October 2016
Gesehen am 23.08.2018